Characterization of the Retro-[3+2] Reaction of Protonated 2, 3′-Bisindolylmethanes by Electrospray Ionization–Tandem Mass Spectrometry. (2nd September 2017) - He, Guang-Yun; Cai, Tian; Xu, Xiao-Ying; Fang, Dong-Mei; Wu, Zhi-Jun
ABSTRACT: Twelve 2, 3′-bisindolylmethanes with various substituents were investigated using electrospray ionization quadrupole time-of-flight tandem mass spectrometry in positive ion mode. A retro-[3+2] reaction was observed in the collision-induced dissociation spectra of protonated 2, 3′-bisindolylmethanes for the first time. The mechanism of retro-[3+2] reaction was concerted or stepwise. For the concerted pathway, carbon–carbon bonds of a protonated compound simultaneously cracked and the m / z 208 ion ([C15 H10 D2 N] + ) was observed with hydrogen–deuterium exchange labeling. The stepwise pathway goes through 1, 3-hydrogen migration twice and the m / z 208 ion ([C15 H10 D2 N] + ) and m / z 207 ion ([C15 H11 DN] + ) were detected with deuterium labeling. In the deuterium-labeled tandem mass spectrum for one compound, only the peak at m / z 208 was present at high abundance, suggesting that the concerted pathway is more likely. In addition, the substituents have no obvious trends on the ratios of the product intensity to the base intensity, further supporting the concerted pathway.